INDOOR AIR QUALITY AND RISK OF RESPIRATORY INFECTIONS AMONG UNDER-FIVE CHILDREN PRESENTING IN TWO HOSPITALS IN IBADAN, NIGERIA (2012)
Acute Respiratory Infection (ARI) is a major cause of morbidity and mortality among under-five children in developing countries. In Nigeria, studies on indoor air quality, particularly, the microflora that are associated with respiratory infections are scanty. This study was therefore designed to determine risk factors in the indoor environment that could predispose under-five children in Ibadan to respiratory infections. A prospective hospital-based case-control study of 220 under-five children each with ARIs (cases) and without ARIs (controls) presenting consecutively in two major hospitals in Ibadan; Oni-memorial Children Hospital and University College Hospital, was carried out. Cases and controls were recruited from January to April, 2010 and matched for age, sex and parent's education. A community-based follow-up of cases and controls was carried out using a checklist to assess indoor housing indicators such as ventilation, temperature and relative humidity. Interviewer-administered four hundred and forty questionnaires were used to elicit information from mothers of under-five children among cases and controls on risk factors for ARIs. Temperature and Relative Humidity (RH) of the livingroom, bedroom and Kitchen were measured between 8-11am using multi-tester N21FR. Airborne microbial samples were collected using non-volumetric method. The total bacterial and fungal counts per cubic metre were determined and compared with the American Industrial Hygiene Association (AIHA) guideline for residential buildings. Data were analysed using descriptive statistics, Chi-square, t-test and logistic regression at p=0.05. Mean ages of cases and controls were 20.4 ±2.5 and 20.9 ± 2.4 months respectively. Mean number of occupants per room among cases was 3.0 ± 1.1 compared to 2.0 ± 0.7 among controls (p<0.05). Forty percent of houses among cases had a minimum of two windows per room compared to 60% among controls (OR=3.3, CI:1.4-10.0). Mean indoor temperature and RH was significantly higher among cases (33.7 ± 1.6 ºC and 66.3 ±5.6%) than controls (31.6 ±1.8ºC and 61.9 ±6.3%). Streptococcus spp. (33.0%, 12.0%), Staphylococcus spp. (35.0%, 22.0%) and Aspergillus spp. (28.0%, 29.0%) were isolated from the indoor air environment among cases and controls respectively. Indoor total bacterial count among cases (9.6x102cfu/m3) was higher than among controls (3.5x102cfu/m3) and the AIHA guideline (?5.0x102cfu/m3) (p<0.05). Indoor fungal count was similar among cases and controls (0.2x102cfu/m3). The livingroom recorded the highest bacterial count of 5.4x102cfu/m3 and 1.4x102cfu/m3 for cases and controls respectively (p<0.05). Under-five children sleeping in same room with more than two adults were found to be twice more likely to develop respiratory infections than those who slept with less than two adults (OR=2.7, CI:1.7-3.6). The use of mosquito coil (OR=1.6, CI:1.0-2.3), lantern (OR=4.1, CI:2.4-6.9) and firewood for cooking (OR=9.3, CI:3.6-24.1) were found to be risk factors for ARIs. Environmental risk factors were higher among cases than controls. These may have contributed to an increased vulnerability to respiratory infections among cases. Health education on adequate ventilation, personal hygiene and good housing conditions are therefore advocated to minimise the risk of respiratory infections associated with poor indoor air quality.